Analysis of Total Flavonoid and Phenol Content from the Combination of Red Spinach (Amaranthus tricolor L.) Ethanolic Extract and Chrysanthemum Flower (Chrysanthemum morifolium) Ethanolic Extract as a Potential Anti-anemic - Kusbandiyah, Jiarti; Angelia Puspadewi, Yuniar; Oktia Maghfiroh, Dinda (Jurnal Pendidikan Keperawatan Indonesia, 2023)
Red spinach and chrysanthemum are two plants that contain various active compounds, including flavonoids and phenols which have good antioxidant activity. One of the benefits of antioxidants is as an anti-anemia. The combination of red spinach and chrysanthemum extracts is expected to be a potential alternative treatment for anemia by combining high Fe and antioxidants found in both herbal ingredients. Research related to test the levels of flavonoids and phenols in red spinach and chrysanthemum extracts (in combination) has not been carried out. This study aimed to measure the total flavonoid and phenol levels of the combination of red spinach ethanol extract (EEBM) and chrysanthemum flower ethanol extract (EEBK). The design of this research is descriptif quantitative. The method used for the extraction is maceration. The solvent used is 70% ethanol. Then the two extracts were combined by mixing the two extracts with a ratio of 5.6 ml EEBM and 1.4 ml EEBK. The process of mixing the extracts was carried out by the centrifugation method. The suspension of the combination of EEBM and EEBK was then measured for the total flavonoid and phenol content. Determination of total flavonoid content (TFC) was carried out using UV-Vis spectrophotometry method with AlCl3 reagent at 425 nm. TFC results are expressed in quercetin equivalent (QE). The TFC result from the combination of EEBM and EEBK was 85.33 mg QE/g. Determination of total phenol content (TPC) was carried out using UV-Vis spectrophotometry method with Folin-Ciocalteu LP reagent at 735 nm. TPC results are expressed in gallic acid equivalent (GAE). The TPC result from the combination of EEBM and EEBK is 25.22 GAE/g. Flavonoids and phenols contained in the combination of EEBM + EEBK extracts can be an alternative anti-anemia because they have the effect of helping the absorption of iron in the intestine